A Class of Commutators for Multilinear Fractional Integrals in Nonhomogeneous Spaces. (11th September 2008) - Lian, Jiali; Wu, Huoxiong
Abstract : Letμ be a nondoubling measure onℝ d . A class of commutators associated with multilinear fractional integrals and RBMO( μ ) functions are introduced and shown to be bounded on product of Lebesgue spaces withμ .